Hepatitis A immunity in refugees in Germany during the current exodus - Jablonka, A; Solbach, P; Happle, C; Hampel, A; Schmidt, R E; Behrens, G M N (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2017)
Germany is facing a huge humanitarian challenge with rapidly rising numbers of refugees entering the country. Data on hepatitis A seroprevalence and infection in refugees and asylum seekers in Europe during the current refugee exodus is scarce. To assess hepatitis A (HAV) seroprevalence and immunity in refugees arriving in northern Germany in 2015. A cross-sectional study of 235 refugees seeking shelter in reception centers in Northern Germany in August 2015 was performed, as acute Hepatitis A had been detected in one refugee in this camp. In order to analyze acute HAV infection and overall immunity, serological screening for HAV antibodies (combined IgG and IgM) was performed. The immunity threshold was defined as <20 IU/l. In all positive screening results, separate IgM testing was performed to detect acute infections. Males accounted for 84.3 % of HAV screened refugees and the mean age of refugees was 29.1 ± 11.2 years. Children and adolescents below the age of 18 years made up 8.8 % of the migrants. Overall HAV immunity within the cohort was 90 %, and a mild age-dependent increase in HAV immunity was observed, with 81.1 % immunity in children <18 years and a 100 % seropositivity in subjects >50 years. One 20-year-old female refugee had positive IgM results with high HAV antibodies, most likely due to subacute HAV infection. This comparably high rate of HAV protected refugees in our cohort supports the notion that the probability of large HAV outbreaks in current German refugee centers is low. However, depending on their current living situation, HAV vaccination should be considered for each refugee child, and healthcare providers and personnel working in refugee centers should be vaccinated against HAV.